Deciphering Co‐Seismic Sedimentary Processes in the Mediterranean Sea Using Elemental, Organic Carbon, and Isotopic Data. (22nd July 2021) - Polonia, A.; Bonetti, C.; Bonetti, J.; Çağatay, M. N.; Gallerani, A.; Gasperini, L.; Nelson, C. H.; Romano, S.
Abstract: Identification of catastrophic events recorded as resedimented deep marine deposits can be challenging because of multiple possible triggering mechanisms. This study investigates seismo‐turbidites (STs) deposited in the Ionian Sea as a consequence of major historical earthquakes related to the Calabrian Arc subduction system. Taking advantage of the available sedimentological reconstructions, we focused our analysis on high‐resolution X‐ray fluorescence core scanner (XRF‐CS), organic carbon and isotopic data to define geochemical signatures characterizing the ST units. The relationships between geochemical and sedimentological proxies were statistically tested using Pearson correlation and principal component analysis (PCA). Up to ∼78% of the total variance in the data set can be reduced to three principal components which identified four elemental ratio groups associated to the degree of terrestrial/coastal influence in each major depositional unit (i.e., pelagic, ST sandy stacked units, homogenites, tsunamite‐seiche laminites, and tsunamite backwash). The sample score results were evaluated together with organic carbon data in order to assess geochemical variability throughout the composite turbidite structure in different basins settings. The basal parts of the ST contain coarse‐grained sediment stacks whose sources can be traced back and sedimentary processes (surficial sediment erosion/massive slope failures) can be defined using geochemical data. The topmost parts of the STs exhibit a mixed compositional character suggesting basin‐wide processes such as seiche oscillations and tsunami wave erosion/backwashing. The application of selected XRF‐CS based elemental ratios as proxies in paleoseismological studies can help reconstruct the seismic history of a continental margin. Plain Language Summary: Submarine paleoseismology is a widely applied method to reconstruct seismicity back in time in tectonically active regions. The Calabrian Arc in the Ionian Sea is a subduction system related to the convergence between Africa and Eurasia plates which produces uplifting coastal mountains, enhances discharge of sediments on the continental shelf and induces the frequent occurrence of earthquakes. Seismic shaking is often associated with submarine slope failures, tsunamis and deposition of seismo‐turbidites which represent more than 90% of total sedimentation in the deep Mediterranean basins. We analyzed physical and geochemical data of sediment samples through a statistical approach to identify elemental ratio groups bringing information on the difference between the interseismic and co‐seismic sedimentary processes, as well as the degree of terrestrial/coastal influence in marine sediments. The proposed statistical approach can be used for sediment characterization, in absence of other analytical data, providing fast information on sedimentary processes and ultimately on the seismic history of the continental margin. Key Points: Analysis of elemental, organic carbon, and isotopic data from seismo‐turbidites provides information on source to sink processes Statistical analysis of physical and geochemical variables enhances correlation of earthquake‐triggered deposits The application of selected geochemical proxies in paleoseismological studies can be very effective in reconstructing past seismicity